Internal homonegativity among men having sex with men: a comparative cross-national study - Shestakovskyi, O.; Kasianczuk, M.; Trofymenko, O.; Chepurko, G.; Djuma, V.; Howell, S. (Социология: теория, методы, маркетинг, 2019)
The paper studies internalized homonegativity (IH) and its predictors among men who have sex with men (MSM) in 12 countries of Eastern Europe and Central Asia (EECA). Internalized homonegativity (sometimes called internal homophobia) is a negative attitude to own same-sex attractions. It arises when gays and other people with homosexual attractions interiorize predominant negative attitudes and assumptions about homosexuals and homosexuality.